Analysis of Factors Influencing Students of the Faculty of Teacher Training and Education, University of Riau in Entrepreneurship - Chairun Nisa; Gimin Gimin; Brilliant Asmit (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The background of this research is the decrease in the number of FKIP students at the University of Riau who are self-employed per year in their class. Therefore it is necessary to know what factors influence Riau University FKIP students in entrepreneurship. The research was conducted by collecting data directly from students using a questionnaire. The sample studied was 78 students who have already started entrepreneurship in the 2020, 2021 and 2022 batches using a purposive-snowball sampling technique. There are 18 variables analyzed using factor analysis to find out what factors are formed in influencing student entrepreneurship. The results showed that among the 18 variables analyzed there were 6 (six) factors that influenced student entrepreneurship. The six factors include technological factors, family factors, perceptions of entrepreneurship, friends, economic conditions, and environmental factors. Of the six factors, the most dominant factor influencing students in entrepreneurship is the technology factor.